ANALISIS EFEKTIVITAS INSTAGRAM SEBAGAI MEDIA PROMOSI RSUD SIDOARJO BARAT DENGAN EPIC MODEL - Nur Rochma Ramadhani; Alshaf Pebrianggara (Jurnal Terapan Ekonomi dan Bisnis, 2026)
The use of social media as a communication and promotion tool for health services has become increasingly important in the digital era. West Sidoarjo Hospital utilizes Instagram to deliver information related to health services, health education, and various hospital activities to the public. Nevertheless, an evaluation of promotional effectiveness is required to ensure that the messages conveyed are well received by the audience. This community service activity aims to evaluate the effectiveness of Instagram promotion at West Sidoarjo Hospital using the EPIC Model, which includes the dimensions of Empathy, Persuasion, Impact, and Communication. The activity employed a quantitative approach through a survey method. Data were collected by distributing questionnaires to 100 followers of the hospital’s Instagram account who met the respondent criteria. The collected data were analyzed using descriptive statistics and multiple linear regression. The results indicate that Instagram promotion at West Sidoarjo Hospital is generally effective. The Communication and Persuasion dimensions contribute     most significantly to promotional effectiveness, while Empathy and Impact function as supporting dimensions. These findings are expected to serve as evaluation material for improving the hospital’s digital communication strategy in accordance with community needs.   Keywords : EPIC Model; the effectiveness of promotions; Instagram; hospitals; Community service